The test of long term returns of value stocks – Does traditional EMH hold or can behavior finance explain the financial market better? - Zhong, Shangrong (2009)
This dissertation tests the long term performance of value investing strategy in the UK stock market. The stock sample of the test is FTSE 100. The time horizon is between the end of 2002 to the end of 2007, altogether 5 years. In addition, this paper is also trying to investigate the controversy between traditional EMH and behavioral finance. As these two theories have close links to value investing strategy, and they provide different explanations to interpret the phenomenon of stock market.